Synthesis and reflections from five CRP evaluations - Report on a meta-analysis of five CRP evaluations - Roth, C.; Zimm, Sophie (CGIAR Independent Evaluation Arrangement, 2016)
With the completion of all CGIAR Research Program (CRP) evaluations in 2016, IEA commissioned a Synthesis to build on the evaluative evidence, aiming to draw lessons and highlight patterns across the completed evaluations.